Effect of Social Media Advertisements on Consumer Purchase Intentions - Raunaq Dash; M Piyushkant (International Journal of Engineering and Management Research, 2020)
The purpose for developing this research paper was to get an in-depth understanding of the mechanisms, features, domains, etc. of social media advertisements, across social media platforms and how these specific things are influencing potential consumers in their buying behavior or in other words their purchase intention. The design of methodology is a mixture of exploratory research design and causal research design, (involving a questionnaire) as the study satisfies both mentioned research design protocols. The findings in terms of the responses (of the questionnaire) collected were intriguing as it depicted that some characteristics of social media advertisements had more impact in influencing their purchase intention, than some of the other. Consumers preferred certain attributes more than some other attributes pertaining to ads on their feeds. Thus, the study of their implications will provide valuable insights to any concerned party. The potential limitations of this research paper will be mainly that the respondents, demographic were limited to a certain figure thus a larger sample size, would make more sense in the future. Also, the practicability of developed hypothesis may vary according to circumstances, which act as a potential limitation. The practical implications of this study can act as a guideline to organizations looking to understand their consumer base, preferences over the social media domain, which could result in potentially building their brand equity.